Coseismic surface displacement variability in relation to lithology - Rondoyanni, Th.; Lykoudi, E.; Kalogeras, E. (Bulletin of the Geological Society of Greece, 2013)
The variability of coseismic surface displacement along reactivated normal faults in the Aegean region is investigated. Seismotectonic data of past earthquakes associated with ground deformation and surface rupturing have been collected and analysed. Geological maps presenting the displacement at different sites along the fault traces have been compiled, as well as plots illustrating the corresponding relation between displacement and lithology. The main conclusion of this work is the strong correlation between regional lithology and coseismic surface displacement. Along a reactivated fault, the displacement observed in the recent geological formations is at least twice the displacement observed in the geological bedrock. It must be noted that the ratio of maximum to minimum displacement values along a certain active fault could be high as 5:1. Moreover, the potential displacements determined on the basis of existing empirical relationships, correspond to those observed in the bedrock. These findings could be taken into consideration in seismic hazard analysis during urban and engineering design.